A Review on the Variables That Influence Product Pricing and Decision - JAIN, DR MANJULA (The journal of contemporary issues in business and government, 2021)
Price is indeed a crucial element of any market and can even be essential to the sustainability of the organization. If the prices are not fixed within line with the target audience chosen, it will adversely impact the earnings of the commodity and the business. The primary purpose of every profit-seeking industry is to create revenue and, within order to accomplish this objective, all aspects relating to inventory management, prices and setting prices require to be handled appropriately. The primary objective of this analysis is thus to examine the factors regarded among organizations in their growth. The selling price for products can be determined by a variety of factors that can be classified into two major categories, internal factors with external factors, all of that are discussed in more depth in this article. In order to address factors that affect international marketing networks, which have been the channels through which products and services meet their global consumers. This indicates that suppliers and customers would either be based in the supplier or buyer nation or be present from both countries. Finally, the paper would address generic ads and regional advertising throughout the global market.